Information and Communication Technology, Hierarchy, and Job Design - Elisa Gerten; Michael Beckmann; Matthias Kräkel (Institute of Labor Economics (IZA), 2022)
In recent decades, information and communication technology (ICT) has been associated with far-reaching changes in the design of jobs. However, it still remains unclear whether these changes will lead to more centralization or more decentralization in firms. Previous literature on this debate has focused on a strict dichotomy between the two possible directions. In contrast, our theoretical and empirical analyses show that equipping employees with ICT leads to both more centralized and more decentralized job-design policies. This finding is particularly pronounced for executive employees, who are granted more work autonomy but also experience more control via stronger monitoring, while non-executive employees only experience more monitoring without receiving more work autonomy. Our theoretical setting is based on a modified principal-agent model. In our empirical approach we apply estimation models that account for both endogeneity and essential heterogeneity, thereby exploiting exogenous geographic variation in our instrumental variable.
Keywords: D2; D86; J3; M1; M5; 330; information and communication technology; centralization; decentralization; monitoring; working from home; marginal treatment effects; essential heterogeneity; instrumental variable